Core Properties of Chitosan and Its Research Progress in Applications to the Medical and Food Industries - Li, Kwongyu (Transactions on Environment, Energy and Earth Sciences, 2026)
This paper explores the advancements and applications of chitosan, a naturally sourced, non-toxic, biocompatible and biodegradable polymer primarily derived from chitin extracted from crustacean exoskeletons and fungal cell walls, in both the medical and food industries. In the medical field, chitosan exhibits significant potentials such as broad-spectrum antimicrobial activity against pathogenic bacteria and fungi, and high utility as a biocompatible, biodegradable carrier in  drug delivery systems. In the food industry, owing to its excellent properties like biodegradability, non-toxicity, and film-forming ability alongside antimicrobial activity, chitosan has been widely applied in food and fruits preservation, often formulated as a coating to block oxygen and inhibit microbial growth, thereby effectively prolonging the shelf life of food and fruits. Moreover, chitosan can be chemically modified or physically combined with other substances like nanoparticles to tailor its properties, such as solubility, mechanical strength and antimicrobial efficiency, for specific applications in both sectors. Overall, chitosan holds great promise for revolutionizing applications in the medicine and food industries, and with further research and development to address current limitations like poor water solubility in neutral environments, its practical value will be further unlocked.
Keywords: Chitosan; biocompatibility; antibacterial activity; medical applications; food Industry.